Penerapan Model Pembelajaran Kooperatif Tipe Student Team Achievement Division (STAD) untuk Meningkatkan Hasil Belajar PAI Siswa pada Materi Mengenal Para Rasul-Rasul Allah SWT di kelas V SDN. No. 026/XI Cempaka Tahun 2016/2017 - Maili Asniar (Jurnal Ilmiah Universitas Batanghari Jambi, 2019)
This study aims to improve the learning outcomes of fifth grade students of SDN. No. 026 / XI Cempaka in 2016/2017 in Islamic Education subjects using the cooperative learning model Student Team Achievement Division (STAD) type. This research was conducted at SDN. No. 026 / XI Cempaka in 2016/2017, Hamparan Rawang District, Sungai Penuh City, Jambi Province. The study was conducted from January to April 2017. This study involved eight class V students. Class action research was conducted in two cycles. Each cycle is conducted in two meetings with four activities, namely planning, implementation, observation, and reflection. Data collected in the form of learning outcomes data collected by tests and observations. The data is then processed by a simple statistical test that is by calculating the class average value and the percentage of mastery learning. The results of the study showed that the use of the STAD cooperative learning model could improve the learning outcomes of fifth grade students of SDN. No. 026/XI Cempaka in 2016/2017 on the subjects of Islamic Education. The average value of students who initially 53.13 increased to 63.75 in Cycle I, and again increased to 75.00 in Cycle II. The percentage of students' mastery learning increased which initially 37.50% increased to 62.50% in Cycle I and again increased to 100.00% in Cycle II. Thus, the STAD type cooperative learning model can be an alternative for teachers to improve student learning outcomes in Islamic Education subjects.